ADVISING OF PARENTS ON QUESTIONS OF FEEDING OF THE CHILD OF FIRST-YEAR OF LIFE - I.I. Ryumina (Педиатрическая фармакология, 2010)
Establishment and maintenance of the contact is a major condition of the successful advising of parents on questions of feeding. An author is divided his own experience with parents not only after the birth of child, but also in the period of pregnancy, as it is particularly important in forming of correct relation of mother to the breast-feeding. The aims of consulting physician are not only a revival of culture of breast-feeding but also providing and control of the correct feeding and care of kid on the first year of life.Key words: advising, breast-feeding, extra feed. (Pediatric Pharmacology. – 2010; 7(3):106-112)